A Geographic Analysis of the Interdisciplinary Collaborations in the Brazilian Scientific Community - Pessoa Junior, Geraldo J. (2022)
Interdisciplinary collaborations have recently attracted the attention of scholars, since they help bridging academic relationships and contribute to make scientific collaboration networks even stronger. However, previous works on this subject have mainly focused on characterizing such interdisciplinary collaborations in specific research groups or scientific communities. In this article, we start from a previous work in which we characterized the interdisciplinary collaborations within the entire Brazilian scientific community, as defined according to the upper level of the knowledge area classification scheme proposed by CNPq, the Brazilian National Council for Scientific and Technological Development, considering the following eight major areas: Agrarian Sciences, Applied and Social Sciences, Biological Sciences, Engineering, Exact and Earth Sciences, Health Sciences, Humanities, and Linguistics, Letters and Arts. Based on this interdisciplinary collaboration network, we conducted a geographic analysis that characterizes how these collaborations have been spread across the Brazilian geographic regions. Overall, our results show strong collaborative ties involving the triad formed by the three main Brazilian geographic regions (Southeast, South and Northeast) for all major areas. Besides, three of the eight major areas (Agrarian Sciences, Biological Sciences, and Health Sciences) show a massive participation in interdisciplinary collaborations across all regions. Despite that, geographic proximity is an important factor, since the proportion of interdisciplinary collaborations involving researchers from the same region is high. Finally, we analyze the patterns of interdisciplinary collaboration by regions and by major areas, thus showing that the Brazilian interdisciplinary network is highly connected.